Zoning Of Modern Markets And Its Effect On Traditional Markets In Sidoarjo - Pujianto, Wahyu Eko; Rodiyah, Isnaini (Opción, 2019)
This research aims to evaluate the policy implementation of zoning modern market. This research uses explanatory research method. Interviews methods with employees of the modern market and government became the basis evaluation. The results showed that there are three factors that affect the implementation of zoning policy of the modern market, like ineffective communication between the government and the owner; misappropriation of licensing and lack of socialization. In conclusion, changes in the lifestyle of the people, especially in terms of shopping who prefer shopping in modern markets than traditional markets led to the modern market are growing rapidly.